Communication Skills Assessment Using Human Avatars: Piloting a Virtual World Objective Structured Clinical Examination. Issue 1 (January 2017) - Kava, Bruce R.; Andrade, Allen D.; Marcovich, Robert; Idress, Thaer; Ruiz, Jorge G.
Abstract : Introduction: : Proficiency in communication skills is a core competency of residency training. We evaluated the feasibility, acceptability and applicability of a virtual world objective structured clinical examination that enables practice based learning and assessment of resident communication skills. Methods: : A virtual clinical encounter situated in 2 practice settings was developed that uses a human avatar physician and a standardized patient. Following an online tutorial house staff participated in 4 communication tasks, including shared decision making, delivering bad news, obtaining informed consent and disclosing a medical error. Validated instruments and semistructured interviews were used to assess house staff acceptability and applicability of the platform. Three faculty members used ACS (Affective Competency Scale) and communication specific assessment instruments to evaluate house staff performance. Results: : A total of 12 urology house staff completed the simulation. Direct costs were approximately 1, 000. The virtual world was easy to use and immersive. Applicability directly correlated with presence (Pearson r = 0.67, p = 0.01) and co‐presence (Pearson r = 0.8, p = 0.002). House staff identified problems with 1) limited nonverbal cues, 2) too much information presented and 3) a lack of immediate feedback. The ICC (intraclass correlation) of faculty assessments was high for ACS at 0.53 (95% CI 0.36–0.69) for single measures, 0.77 (95% CI 0.63–0.86) for average measures and less for other assessment instruments. Conclusions: : A virtual world objective structured clinical examination is a feasible, acceptable and applicable method of communication skills assessment. Improving nonverbal cues, focusing on individual skill sets and providing immediate feedback are measures to be adopted in future iterations of this platform.